2008
DOI: 10.1074/jbc.m708873200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination and Degradation of Homeodomain-interacting Protein Kinase 2 by WD40 Repeat/SOCS Box Protein WSB-1

Abstract: Homeodomain-interacting protein kinase 2 (HIPK2) is a member of the nuclear protein kinase family, which induces both p53-and CtBP-mediated apoptosis. Levels of HIPK2 were increased by UV irradiation and cisplatin treatment, thereby implying the degradation of HIPK2 in cells under normal conditions. Here, we indicate that HIPK2 is ubiquitinated and degraded by the WD40-repeat/SOCS box protein WSB-1, a process that is blocked under DNA damage conditions. Yeast two-hybrid screening was conducted to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 51 publications
(57 reference statements)
2
90
1
Order By: Relevance
“…In particular, we showed that this proapoptotic phenotype of MYCN-overexpressing cells also required p53 phosphorylation at serine 46 and were associated to a more pronounced activation of proapoptotic target genes compared with those involved in cell cycle arrest, such as the p21 WAF1 , in keeping with the current understanding of p53 activity (32,33). Among a few kinases able to phosphorylate p53 S46 , we focused our attention on HIPK2, a protein required for apoptosis induced by neurotrophin deprivation in developing sympathetic neurons (45), whose role in p53 S46 phosphorylation and p53-dependent apoptosis has clearly been established (26,36 (37)(38)(39)(40). DNA damage was shown to promote HIPK2 accumulation through an ATM/ATRdependent inhibition of its degradation by Siah1 and/or WSB1 ubiquitin ligases (38,40).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, we showed that this proapoptotic phenotype of MYCN-overexpressing cells also required p53 phosphorylation at serine 46 and were associated to a more pronounced activation of proapoptotic target genes compared with those involved in cell cycle arrest, such as the p21 WAF1 , in keeping with the current understanding of p53 activity (32,33). Among a few kinases able to phosphorylate p53 S46 , we focused our attention on HIPK2, a protein required for apoptosis induced by neurotrophin deprivation in developing sympathetic neurons (45), whose role in p53 S46 phosphorylation and p53-dependent apoptosis has clearly been established (26,36 (37)(38)(39)(40). DNA damage was shown to promote HIPK2 accumulation through an ATM/ATRdependent inhibition of its degradation by Siah1 and/or WSB1 ubiquitin ligases (38,40).…”
Section: Discussionmentioning
confidence: 99%
“…Among a few kinases able to phosphorylate p53 S46 , we focused our attention on HIPK2, a protein required for apoptosis induced by neurotrophin deprivation in developing sympathetic neurons (45), whose role in p53 S46 phosphorylation and p53-dependent apoptosis has clearly been established (26,36 (37)(38)(39)(40). DNA damage was shown to promote HIPK2 accumulation through an ATM/ATRdependent inhibition of its degradation by Siah1 and/or WSB1 ubiquitin ligases (38,40). Oncogene-dependent replication stress was also shown to induce DNA damage and ATM/ATR activation leading to p53-dependent apoptosis (or senescence), suggesting that DDR might represent an endogenous anticancer barrier contrasting transforma- tion induced by several oncogenes (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIPK2 downregulation during hypoxia strongly reduces ADR-induced p53Ser46 phosphorylation, moreover, it allows the HIPK2 elimination from promoter-associated repressor complexes with induction of a substantial fraction of hypoxia-induced genes such as PDK1, TGFB3, CYP1B1 (cytochrome P450) (Calzado et al, 2009a) and hypoxia-induced factor (HIF)-1a (Nardinocchi et al, 2009). Other ubiquitin ligases involved in HIPK2 downregulation may take place during hypoxia including WD40-repeat/SOCS box protein WSB-1 (Choi et al, 2008), which is a novel predicted HIF1 target gene, as identified by an integrative genomic approach, upregulated upon hypoxia (Benita et al, 2009); and the RING family member Siah-1, originally identified along with Siah-2 as HIPK2-interacting protein (Winter et al, 2009;Calzado et al, 2009a). As for WSB-1 and Siah-2, Siah-1 depletion by siRNA partially inhibits hypoxia-induced HIPK2 degradation (Moehlenbrink et al, 2010).…”
Section: Hipk2 Inactivation In Tumors and P53 Dysfunctionmentioning
confidence: 99%